THE EFFECT OF PERCEIVED USEFULNESS , EASE OF USE AND SECURITY ON INTEREST IN USING BSI MOBILE SERVICES WITH TRUST AS INTERVENING VARIABLE (CASE STUDY ON UINSU MEDAN STUDENTS) - Maryam Batubara; Nurul Jannah; Annisa Lestari Ritonga (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
This study aims to analyze the effect of perceived usefulness, ease of use, and security on interest in using BSI Mobile services with trust as intervening variable. The number of respondents in this study were 100 students of UINSU Medan who did not have a BSI Mobile account. The method used to collect the data is by distributing questionnaires through the google form. Then the data were processed by SPSS Statistics Version 26. The result showed that perceived usefulness had a significant effect on interest, as can be seen from the value of α (0,007 < 0,05) and the value of t count 2,778 > t table 1,988. Ease of use had no effect on interest, as can be seen from the value of α (0,718 > 0,05) and the value of t count 0,362 < t table 1,988. Security had a significant effect on interest, as can be seen from the value of α (0,007 < 0,05) and the value of t count 2,781 > t table 1,988. Trust had a significant effect on interest, as can be seen from the value of α (0,000 < 0,05) and the value of t count 4,707 > t tabel 1,988. Perceived usefulness had a significant effect on interest through trust, as can be seen from the value of t count 3,605 > t table 1,661. Ease of use had a significant effect on interest through trust, as can be seen from the value of t count 2,501 > t table 1,661 and security has a significant effect on interest through trust as can be seen from the value of t count 3,306 > t tabel 1,661.